2020
DOI: 10.1111/ina.12635
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sick building syndrome symptoms and its associated factors among bank employees in Pokhara Metropolitan, Nepal

Abstract: A cross‐sectional study was conducted to assess the prevalence of sick building syndrome symptoms and its associated factors among bank employees. Data were collected through a self‐administered MM040NA questionnaire among 234 employees of commercial banks in Pokhara Metropolitan, Nepal. The prevalence of general, ocular, respiratory, and dermal sick building syndrome symptoms was 47.6%, 11.9%, 11.9%, and 8.1%, respectively. The perceived indoor physical environment was a significant predictor of sick building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
3
13
1
1
Order By: Relevance
“…Carbon dioxide and poor ventilation seem to be the main causes of SBS 6,36 . In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms 37 . However, other possible reasons remain unclear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Carbon dioxide and poor ventilation seem to be the main causes of SBS 6,36 . In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms 37 . However, other possible reasons remain unclear.…”
Section: Discussionsupporting
confidence: 88%
“…6,36 In line with the literature, we demonstrated the impact of insufficient ventilation on symptoms. 37 38,39 The dose-response relationship is typically evaluated to investigate the causes of the onset of SBS symptoms.…”
Section: Sick Building Syndrome Work Environment and Ventilation Workmentioning
confidence: 99%
“…24 Studies with focus on sick building syndrome (SBS) symptoms have reported a 3%-9% prevalence of facial skin symptoms (dry or flushed facial skin, facial rash, facial itching, or facial skin irritation) in Sweden. [25][26][27][28][29][30][31] Studies from other countries, including Ethiopia, 32 Japan, 33 and Nepal, 34 reported a lower prevalence of dry or flushed facial skin, from 1% to 4%. Seborrheic dermatitis affects the scalp as well as face, retro-auricular area, and the upper chest, causing flaking, scaling, inflammation, and pruritus, and can have marked erythema.…”
Section: Introductionmentioning
confidence: 99%
“…Algılanan iç mekân fiziksel çevre ise, hasta bina sendromu semptomlarının önemli bir öngörücüsü olarak değerlendirilmiştir. Bunun yanı sıra yaş, sıcaklıktan rahatsızlık ve iş basıncı, genel semptomlarla önemli ölçüde ilişkilendirilmiş ve çalışanların hasta bina sendomu semptomlarından muzdarip olmasını önlemek ve kontrol etmek için oda sıcaklığının, gürültü kontrolünün, iyi havalandırma sisteminin uygun şekilde korunması ve bankalarda destekleyici psikososyal çalışma ortamının teşvik edilmesinin önemli olduğu değerlendirilmiştir (Dhungana, Chalise, 2020). Amerikan Çevre Koruma Ajansı (EPA) verilerine göre ilk 10 sağlık sorunu arasında Hasta Bina Sendromunun, 4. sırada yer aldığı ve mutlaka mücadele edilmesi gerektiği belirtilmektedir (Agca, 2005).…”
Section: Hasta Bi̇na Sendromu Ve Semptomlariunclassified